(untitled) (Research, Society and Development, 2020)
The purpose of the study was to evaluate the antioxidant activity, rheological behaviour, oxidative stability, and antibacterial potential of coffee oils (Coffea arabica L.). The extraction process took place from green and roasted beans, by cold pressing, and filtration via filtering card. The experimental design consisted of five treatments: R100 (100% roasted oil); R75G25 (75% roasted oil and 25% green oil); R50G50 (50% roasted oil and 50% green oil); R25G75 (25% roasted oil and 75% green oil), and G100 (100% green oil). The treatment R75G25 showed a higher content of total phenolic compounds and higher DPPH• and ABTS•+ anti-radical efficiency. Regarding rheological behaviour, all coffee oils can be characterized as Newtonian fluids because the shear stress and strain rate varied linearly, with the line intersecting at zero. The treatments R75G25 and R25G75 showed a longer oxidation induction time, in the oxidative stability analysis, in addition to antibacterial activity having been verified for all oil samples. Besides that, the investigated green and roasted coffee oils are sources of fatty acids, including from the omega 3, 6, and 9 classes. Therefore, the use of arabica coffee oil mixtures as natural preservatives in food can be considered a promising alternative for the partial replacement of chemical additives in food matrices and in cosmetic formulations allowing the development of innovative products.